Does government digitization contribute to economic growth? Empirical evidence from 109 countries - Ding, Yemin; Chin, Lee; Taghizadeh-Hesary, Farhad; Yan, Xiaohan (Technological and Economic Development of Economy, 2025)
In the digital age, governments worldwide are increasingly turning to digitization to enhance efficiency and foster economic growth. This study investigates the impact of government digitization on economic growth, addressing the pressing issue of how digital transformations within the public sector can drive economic growth. First, we empirically estimate panel data from 2002 to 2021 across 109 countries using multiple statistical methods, consistently supporting that government digitization can significantly promote economic growth. Subsequently, mechanism tests are conducted using two fixed effect models containing interaction terms, revealing that government digitization can foster economic growth by curbing corruption and reducing the time businesses need to access public services. Furthermore, heterogeneity analysis confirms the moderating effects of telecommunications infrastructure, basic education popularization, natural resource abundance, government efficiency, democracy, and ruling party ideology on the relationship between government digitization and economic growth. Lastly, quantile regression reveals a nuanced pattern, indicating that as a country’s economic development level increases, the promoting effect of government digitization on economic growth initially rises before declining. These findings provide new insights for governments worldwide seeking economic growth.First published online 04 July 2025